Dudley Howard Williams. 25 May 1937 — 3 November 2010. (31st December 2017) - Sanders, Jeremy K. M.; Robinson, Dame Carol V.
Abstract : Dudley Williams was a pioneer in using nuclear magnetic resonance (NMR) spectroscopy and mass spectrometry (MS) to solve important structural problems in Chemistry and Biology. His 35-year quest to understand the structure and mode of action of the vancomycin antibiotics led him to fundamental thinking about the nature and thermodynamics of molecular recognition, in particular the roles of solvation, flexibility, entropy, enthalpy and cooperativity. He was always keen that his expertise be used for practical benefit through his academic research and industrial consulting. His legacy also includes a set of textbooks that transformed the use of spectroscopic methods in organic chemistry, and a school of former PhD students and postdoctoral colleagues who have themselves made major contributions across a broad swathe of science.